Causal Attributions in an Australian Aboriginal Family With Marfan Syndrome: A Qualitative Study - McInerney-Leo, Aideen M.; West, Jennifer; Meiser, Bettina; West, Malcolm; Brown, Matthew A.; Duncan, Emma (Frontiers in Genetics, 2020)
Causal attributions are important determinants of how health threats are processed and affect health-related behaviours. To date, there has been no research on causal attributions in genetic conditions in Aboriginal Australians. Forty members of a large Aboriginal Australian family with Marfan syndrome (MFS) were invited to participate in an ethically approved study exploring causal attributions, including perceived causes of phenotypic variability within the family. Eighteen individuals consented to conduct semi-structured qualitative interviews, which were recorded, transcribed verbatim and analysed thematically. Most participants knew that MFS was genetic, but there were diverse theories about inheritance, including beliefs that it skipped generations, was affected by birth order and/or gender, and that it co-occurred with inheritance of blue eyes within this family. The mutation was thought to have been inherited from British settlers and initially triggered by disease or diet. Factors believed to modify disease severity included other genes and lifestyle factors, particularly alcohol and substance abuse and stress. Generally, this family did not endorse “blaming” chance or a higher power for phenotypic variability, though some felt that the spirits or a deity may have played a role. In conclusion, although participants knew MFS was a genetic condition, many speculated about the role of non-genetic causes in initiating the original mutation; and the gene-environment interaction was thought to affect severity. This study demonstrates a successful approach for exploring causal attributions in other genetic conditions in First Australians.